2014
DOI: 10.3390/molecules19055692
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal Evaluation of Tetrahydroprotoberberine and Spirocyclic Erythrina-Alkaloids

Abstract: Leishmaniasis is one of the World's most problematic diseases in developing countries. Traditional medicines to treat leishmaniasis have serious side effects, as well as significant parasite resistance problems. In this work, two alkaloids 1 and 2 were obtained from Corydalis govaniana Wall and seven alkaloids 3-9, were obtained from Erythrina verna. The structures of the compounds were confirmed by mass spectrometry and 1D-and 2D-NMR spectroscopy. The leishmanicidal activity of compounds 1-9 against Leishmani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…All the alkaloids employed in this study were obtained from E. verna as previously described in Callejon et al …”
Section: Methodsmentioning
confidence: 99%
“…All the alkaloids employed in this study were obtained from E. verna as previously described in Callejon et al …”
Section: Methodsmentioning
confidence: 99%
“…Callejon et al () isolated seven alkaloids from E. verna barks, which were tested against Leishmania amazonensis . Erythraline ( 40 ), 8‐oxo‐erythraline epoxide ( 44 ), crystamidine ( 45 ), and erythrinine ( 42 ) showed leishmanicidal activity with an IC 50 around 40–70 μg/ml, although these alkaloids also presented low selectivity index (CC 50 drug/IC 50 drug) when tested in macrophage cells (J774), indicating cytotoxicity for mammalian cells.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In addition, the study showed the effects of alcoholic extract against trypomastigote forms, reducing the number of parasites at 80% at 1,000 μg/ml. At the same concentration, the cytotoxic effects in macrophages for alcoholic extract of E. speciosa were not observed Callejon et al (2014). isolated seven alkaloids from E. verna barks, which were tested against Leishmania amazonensis.…”
mentioning
confidence: 99%
“…It is suggested that the GOV hydroxylation takes place at C (14), which tends to favor the formation of the m/z 324 by H 2 O loss with only a relatively small amount of m/z 194 by a RDA reaction. Considering the hydroxylation in different positions, like C(5) or C(6), both reactions (H 2 O loss and RDA) will not affect the occurrence of each one, or if it were in the positions C (8) or C (13), just one of the two reactions would be possible. Based on these data, M3 was tentatively proposed to be a mono-hydroxylated metabolite (Fig.…”
Section: Metabolite Identificationmentioning
confidence: 99%
“…[7], a glabrous herb distributed in the Himalayas of Nepal, Pakistan and India [4,7]. GOV has been reported to show a different number of biological activities including anti-urease [7], leishmanicidal [8] and antinociceptive [4]. These activities have inspired the conduction of a study regarding its pharmacokinetic profile and in vitro metabolism.…”
Section: Introductionmentioning
confidence: 99%